Students’ Gendered Expectations and Evaluation on Thesis Advising Skills and Mentoring Practices of the Local Thesis Advisory Committee (LTAC) in Camarines Norte State College - Mabeza, Ma. Reina A. (Journal of Social Knowledge Education (JSKE), 2025)
Purpose of the study: To analyze the students' gendered expectations and evaluation on advising skills and mentoring practices of the Local Thesis Advisory Committee (LTAC) members in the Camarines Norte State College situated in Daet, Camarines Norte, Philippines for academic year 2022-2023. Methodology: The study used descriptive quantitative research design. The respondents of the study were comprised of 42 male, 55 female, and 8 LGBTQ+. A face-to-face interview using survey questionnaire was employed to gather the data and data gathered were analyzed using frequency and percentage distribution as well as the computation of mean. The results were presented in tabular format. Main Findings: The findings revealed differences in preferences for advisor traits as males expected expertise and logical presentation skills, females wanted more guidance in developing the topic and structuring analysis, while LGBTQ+ students desired compassion, interest, and constructive feedback. The male group evaluated advisors as excellent in intelligence and inquisitiveness, while female group in honesty, explicitness, and refined feedback, and for LGBTQ+ advisers as excellent in compassion. All groups faced challenges securing approval and navigating panel perspectives. Novelty/Originality of this study: This study reveals that students, regardless of gender, recognized the importance of advising and mentoring in successfully completing the undergraduate theses. It also emphasizes how higher education institutions can address gender equality and improve thesis writing policies, ensuring that all student across gender groups receive tailored support for a more effective advising experience.